EKSISTENSI SENI PERTUNJUKAN LUAMBEK DALAM KEHIDUPAN MASYARAKAT NAGARI KEPALA HILALANG KECAMATAN 2 X 11 KAYU TANAM KABUPATEN PADANG PARIAMAN - Zahara Kamal (Jurnal Elektronik WACANA ETNIK, 2012)
Luambek is a performance art tradition which is an integral part of socio-cultural life of Nagari Kepala Hilalang. For the people, this social ceremony enlivened by Luambek called Alek Pauleh, which create a social force in the nagari and reflect direct relationship within social structure. The existence of Luambek is related to the ownership of art itself. Furthermore, Luambek is positioned as "suntiang niniak-mamak, pamenan anak-mudo mudo" (jewelery of ninik-mamak or traditional leaders, elders, and children's game).